PENERAPAN UPAYA PREVENTIF POSISI ANGKAT ANGKUT UNTUK MENGHINDARI TERJADINYA NYERI PUNGGUNG BAWAH DI POSYANDU SUMUR REJO GUNUNG PATI - Shella Dhika Rahmawati; Ni Kadek Krisna Dwi Patrisia; Almita Ratu Rifanda; Sofia Mardiana; Friesca Persityara Agatha; Aulia Ayu Kusuma W. (Pusat Riset dan Inovasi Nasional, 2022)
Low back pain is a condition where the lower back feels very painful and can result in hampering activities. Based on the data obtained, the community in the Gunung Pati area works as a porter and often feels pain in their lower back. Usually residents only apply balsam if they feel lower back pain. There are still many residents who underestimate these complaints and many residents are wrong when lifting heavy items.